Employee influencer management: evidence from state-owned enterprises in Indonesia. Issue 2 (19th April 2022) - Arief, N. Nurlaela; Gregory, Anne; Pangestu, Aria Bayu; Ramdlany, Dany Muhammad Athory; Sanjaya, I Made Ariya
Abstract : Purpose: The purpose of this study is to explore how Indonesian state-owned enterprises (SOEs) select and "manage" employee influencers in order to engage more effectively with younger generations. Design/methodology/approach: The study applies a mixed-methods approach. Quantitative data were obtained by analyzing Instagram content with samples for analysis being taken from company-related posts from June 2018 to June 2020. Qualitative data collection was by two focus group discussions (FGD). The FGDs comprised in total, 22 employee influencers representing the 11 sectors of SOEs in Indonesia. Findings: The article examines how employee influencers engage with others; how they are chosen by their organizations; how they are managed and the support they need from their employers. It was discovered that a careful triangulation is required between employees as influencers, their followers and SOE communication hubs. A key factor is maintaining the authentic relationship between employee influencers and their followers. A conceptual model of employee influencer management for Indonesia is proposed. Research limitations/implications: The research provides useful insights for communication management, marketing, and human resources in developing and supporting the role of employee influencers. Practical implications: The research provides useful insights for communication management, marketing and human resources in developing and supporting the role of employee influencers. The suggested model is of practical utility for SOEs for managing employee influencers in Indonesia and provides valuable indicators for other countries. Originality/value: The study of SOEs' employee influencers has not been explored previously in the literature. This, combined with the Indonesian perspective, brings new insights to the field. Social media use is especially high in Indonesia, so it acts as a good exemplar for the field. It also builds on the growing literature about the importance of employees as influencer, especially in the social media space. The model also make a theoretical contribution.